2022
DOI: 10.3390/microorganisms10050960
|View full text |Cite
|
Sign up to set email alerts
|

Small Intestine Bacterial Overgrowth Can Form an Indigenous Proinflammatory Environment in the Duodenum: A Prospective Study

Abstract: Small intestinal bacterial overgrowth (SIBO) contributes to the formation of an inflammatory environment in various intestinal and extraintestinal diseases. Cytokines that participate in these mechanisms are yet to be examined. Upper gastrointestinal endoscopy with duodenal aspiration was performed in 224 patients. Quantitative cultures of aerobic species were performed, concentrations of interleukin 1β (IL-1β), interleukin 6 (IL-6), and tumor necrosis factor alpha (TNF-α) were measured, and loads of Escherich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The deregulation of any of these protective mechanisms can lead to microbiota dysbiosis, a potential pathway for the development of Small Intestinal Bacterial Overgrowth (SIBO) [ 2 , 3 ]. SIBO is characterized by increased colonization of anaerobic and aerobic microorganisms within the small intestine, predominantly Gram-negative species including Klebsiella pneumoniae, Escherichia coli , Streptococcus gramineus , Prevotella , Clostridium spp, and Methanobrevibactersmithii [ 4 , 5 , 6 ]. Depending on the dominant composition of the bacterial overgrowth, the production of gases as a result of bacterial fermentation, such as hydrogen (H 2 ), methane (CH 4 ), or hydrogen sulfide (H 2 S) is observed.…”
Section: Introductionmentioning
confidence: 99%
“…The deregulation of any of these protective mechanisms can lead to microbiota dysbiosis, a potential pathway for the development of Small Intestinal Bacterial Overgrowth (SIBO) [ 2 , 3 ]. SIBO is characterized by increased colonization of anaerobic and aerobic microorganisms within the small intestine, predominantly Gram-negative species including Klebsiella pneumoniae, Escherichia coli , Streptococcus gramineus , Prevotella , Clostridium spp, and Methanobrevibactersmithii [ 4 , 5 , 6 ]. Depending on the dominant composition of the bacterial overgrowth, the production of gases as a result of bacterial fermentation, such as hydrogen (H 2 ), methane (CH 4 ), or hydrogen sulfide (H 2 S) is observed.…”
Section: Introductionmentioning
confidence: 99%
“…IL-1β has also been implicated in the pathophysiology of TBI and its associated symptoms [25]. The studies from this meta-analysis suggest that the significantly increased IL-1β levels reported in mTBI patients are associated with the acute phase of inflammatory response and could indicate its role in the pathophysiology of mTBI.…”
Section: Discussionmentioning
confidence: 76%
“…IL-1β is involved in various physiological and pathological processes, including inflammation, fever, tissue repair, and immunity, acting on various target cells, including endothelial cells, fibroblasts, and immune cells, by binding to the IL-1 receptor (IL-1R) and activating intracellular signaling pathways. IL-1β promotes the production of other proinflammatory cytokines, such as TNF-α and IL-6, and induces the expression of adhesion molecules and chemokines, which attract immune cells to the site of injury or infection [25]. Changes in IL-1β functions have been implicated in various diseases, including rheumatoid arthritis, type 2 diabetes, and Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β is involved in various physiological and pathological processes, including inflammation, fever, tissue repair, and immunity, acting on various target cells, including endothelial cells, fibroblasts, and immune cells, by binding to the IL-1 receptor (IL-1R) and activating intracellular signalling pathways. IL-1β promotes the production of other proinflammatory cytokines, such as TNF-α and IL-6, and induces the expression of adhesion molecules and chemokines, which attract immune cells to the site of injury or infection [25]. Changes in IL-1β functions have been implicated in various diseases, including rheumatoid arthritis, type 2 diabetes, and Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%